2018
DOI: 10.5897/jcreo2012.012
|View full text |Cite
|
Sign up to set email alerts
|

Human natural killer (NK) cell activation by luteolin from Brucea javanica leaves

Abstract: There is growing interest in using natural substances from plants to potentially enhance anticancer activity. A key target in this respect is natural killer (NK) cells in order to generate an anticancerimmune response. Luteolin used in this study was derived from a local plant Brucea javanica leaves extract; through a bioassay-guided fractionation. The expression of interleukin-2 (IL-2) and interferon-γ (IFN-γ) was increased after 20 h treatment of 0.1 µM luteolin in human mixed lymphocytes, which reflects the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 14 publications
(14 reference statements)
0
1
0
Order By: Relevance
“…The authors also demonstrated that the enhanced killing was due to the increased secretion of cytokine IL-2 and interferon. 17…”
Section: Discussionmentioning
confidence: 99%
“…The authors also demonstrated that the enhanced killing was due to the increased secretion of cytokine IL-2 and interferon. 17…”
Section: Discussionmentioning
confidence: 99%